A.Yuldoshev's Story "Puancare" Magical - Philosophical Work - Matmusayeva Nadira Mamirovna (Genius Publishing Group, 2022)
This article analyzes the peculiarities of the new trends in Uzbek prose during the years of independence on the basis of A.Yuldashev's story "Poincaré".
Keywords: story; narrative; figurative; formula of the universe